Board Characteristics And Real Performance In Malaysian State-owned Enterprises (soes) - Fekri Ali Shawtari,; Muslim Har Sani Mohamad,; Hafiz Majdi Abdul Rashid,; Abdullah Moh’d Ayedh (Emerald Group Publishing, 2024)
Non-Indexed Publication